2022
DOI: 10.1186/s12877-022-03003-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospital-acquired adverse drug reactions: a cohort of Ugandan older adults

Abstract: Background Globally, it is estimated that the number of older adults will become 2 billion by 2050. The identification of the predictors of adverse drug reaction (ADR) in hospitalized older patients is crucial to the development of prediction tools and preventive strategies to mitigate the burden of ADRs. This study aimed to determine the predictors of hospital-acquired ADR occurrence among hospitalized older adults in a low-income country. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Of 78 studies, 27 studies [ 18 44 ] were carried out among general patients, while the remaining studies [ 45 95 ] were carried out among specific patients. Seventeen studies [ 18 22 , 24 , 26 , 31 , 33 35 , 38 , 39 , 41 – 43 , 51 ] reported the prevalence of ADEs leading to hospital admissions, while 30 studies [ 18 , 19 , 22 33 , 35 , 37 41 , 43 , 44 , 65 , 80 , 85 88 , 91 , 95 ] reported the prevalence of ADEs during hospitalization. Twelve studies [ 18 , 19 , 22 , 24 , 26 , 31 , 33 , 35 , 38 , 39 , 41 , 43 ] reported ADE occurrence in both settings.…”
Section: Resultsmentioning
confidence: 99%
“…Of 78 studies, 27 studies [ 18 44 ] were carried out among general patients, while the remaining studies [ 45 95 ] were carried out among specific patients. Seventeen studies [ 18 22 , 24 , 26 , 31 , 33 35 , 38 , 39 , 41 – 43 , 51 ] reported the prevalence of ADEs leading to hospital admissions, while 30 studies [ 18 , 19 , 22 33 , 35 , 37 41 , 43 , 44 , 65 , 80 , 85 88 , 91 , 95 ] reported the prevalence of ADEs during hospitalization. Twelve studies [ 18 , 19 , 22 , 24 , 26 , 31 , 33 , 35 , 38 , 39 , 41 , 43 ] reported ADE occurrence in both settings.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the risk of gastrointestinal side effects in nonsteroidal anti-inflammatory drugs (NSAIDs) could be increased if previous NSAID intolerance was identified 29 . In hospitalised older patients, a history of experiencing harmful outcomes from medications in the preceding year was shown to predict adverse drug effects from current medications 30 . A study on treatment-resistant depression also found that a history of electroconvulsive therapy and unsuccessful antidepressant trials were associated with the outcome of vagus nerve stimulation 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies among admitted elderly patients have reported cardiovascular drugs, nervous system agents and anti-infective agents as the cause of ADRs. 11 , 12 A study in Uganda by Kiguba et al 17 reported herbal medicines to be linked to hospital-acquired ADRs. The Uganda treatment guidelines require that misoprostol is administered from a hospital setting; however, it is a common practice for patients to self-medicate with misoprostol to initiate abortion before seeking professional care which causes adverse events such as incomplete abortion, failed abortion, missed abortion, severe anaemia, haemorrhagic shock, sepsis, ectopic pregnancy and ruptured uterus 26 requiring hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 10 Recent studies in Uganda among the admitted elderly implicate cardiovascular drugs, nervous system agents and anti-infective agents as the common cause of ADRs. 11 , 12 Self-medication has been highlighted to be associated with ADR-related hospitalization in HIC 13 , 14 ; however, such data are scarce in Sub-Saharan Africa (SSA) where self-medication is rampant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation